2017
DOI: 10.1177/1073191117721743
|View full text |Cite
|
Sign up to set email alerts
|

Parent Ratings of the Strengths and Difficulties Questionnaire: What Is the Optimum Factor Model?

Abstract: To date, at least 12 different models have been suggested for the Strengths and Difficulties Questionnaire (SDQ). The current study used confirmatory factor analysis to examine the relative support for these models. In all, 1,407 Malaysian parents completed SDQ ratings of their children (age range = 5-13 years). Although the findings showed some degree of support for all 12 models, there was most support for an oblique six-factor model that included the five SDQ domains (emotional problems, conduct problems, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 48 publications
(118 reference statements)
3
32
1
Order By: Relevance
“…The support for the 2-factor model in the study differs from the originally theorized 5factor model, with the ES, CP, HY, PP and PS items loading on their own respective factors (R. Goodman, 1997Goodman, , 2001. Although this does not reflect any of the other 11 SDQ models reviewed by Gomez and Stavropoulos (2017), the present model has some semblance with one of the model they reviewed. In that model, initially proposed by Palmieri and Smith (2007), there is (like our study) a positive construal factor comprising all the 10 positive worded items.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The support for the 2-factor model in the study differs from the originally theorized 5factor model, with the ES, CP, HY, PP and PS items loading on their own respective factors (R. Goodman, 1997Goodman, , 2001. Although this does not reflect any of the other 11 SDQ models reviewed by Gomez and Stavropoulos (2017), the present model has some semblance with one of the model they reviewed. In that model, initially proposed by Palmieri and Smith (2007), there is (like our study) a positive construal factor comprising all the 10 positive worded items.…”
Section: Discussioncontrasting
confidence: 80%
“…For more detailed description of the participants and procedure, the reader is encouraged to refer to Gomez and Stavropoulos (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that boys scored higher than girls on the Total Difficulties score [45]. Also, Gomez and Stavropoulos found that a six-factor model with a positive construal factor encompassing the reverse-coded items and Prosocial Behavior factor was the best fit for Malaysian parents [46]. They also noted that the standard five-factor model showed a good fit, and that all 12 models tested had adequate fits with the sample of Malaysian parents [46].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Gomez and Stavropoulos found that a six-factor model with a positive construal factor encompassing the reverse-coded items and Prosocial Behavior factor was the best fit for Malaysian parents [46]. They also noted that the standard five-factor model showed a good fit, and that all 12 models tested had adequate fits with the sample of Malaysian parents [46]. However, Stokes and colleagues failed to validate previously identified SDQ factor structures with a sample of Malaysian children, parent, and teacher triads; rather, the authors conducted a split sample exploratory factor analysis (EFA), producing a three-factor structure, which was partially supported in confirmatory factor analysis (CFA) [47].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent to this, most recently used ADHD rating scales have the 18 ADHD symptoms, word-to-word, as presented in DSM-IV, but with the word often omitted in the description of the symp-toms. [4] ADHD rating scales are often used in research and clinical settings. In that line, Burns, Walsh, Servera, Lorenzo-Seva, Cardo and Rodrguez-Fornells (2013) have noted that ADHD rating scales have made extensive contributions to our knowledge and understanding of ADHD.…”
Section: Introductionmentioning
confidence: 99%